Time series econometrics in a post-acquisition antitrust analysis: The Brazilian iron ore market - Eduardo P. S. Fiuza; Fabiana F. M. Tito (Institute for Applied Economic Research (ipea), 2015)
In Brazil, mergers and acquisitions are usually analyzed by the Antitrust Authorities ex post, following a SCP framework close to the Merger Guidelines applied in the USA. However, this framework was unable to address a set of acquisitions of four mining companies by the newly privatized national champion CVRD. The present article reports an econometric exercise undertaken by the Brazilian Ministry of Justice, which came to reinforce the definition of the relevant geographic market and to test for structural breaks in the price series. Though international prices Grangercaused domestic prices in Brazil, they explain less than a third of the variance. A price surge on the acquired miners' series was observed above the export price increase not long after the acquisitions, such that a structural break could not be rejected.
Keywords: L49; L61; C32; 330